3D smart user interactive system with real-time responding tele-robotic proprioceptive information - Tee, Tiam Hee *; Eu, Kok Seng *; Yap, Kian Meng *; Marshall, Alan; Lee, Tsung-Han (2013)
Feedback of proprioceptive information is essential for many tele-robotic systems, especially those designed to undertake tasks concerning hazardous environments and for efficient out-of-sight remote control applications. Given highly sensitive nature of these applications, even small errors (e.g. less than one degree of displacement in robot posture) can cause unnecessary risk. Thus, accurate feedback of proprioceptive information, as well as a technique to precisely interpret this information, is significant to operator. In this paper, we introduce a framework that uses pulse feedback mechanism to measure the proprioceptive information of a robot operating over real-time wireless communication and represent it in 3D model user interface. The 3D user interface enhances the interpretation of proprioceptive information to help operator to visualize the real-time relative position of the robot. The paper also provides results that demonstrate how the framework allows synchronization between 3D model and tele-robot to be achieved in real-time over wireless communications.